2017
DOI: 10.1371/journal.pone.0183067
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric proteins tagged with specific 3xHA cassettes may present instability and functional problems

Abstract: Epitope-tagging of proteins has become a widespread technique for the analysis of protein function, protein interactions and protein localization among others. Tagging of genes by chromosomal integration of PCR amplified cassettes is a widely used and fast method to label proteins in vivo. Different systems have been developed during years in the yeast Saccharomyces cerevisiae. In the present study, we analysed systematically a set of yeast proteins that were fused to different tags. Analysis of the tagged pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Since tags can interfere with protein function [31], we next tested the spread of untagged GA DPRs using GA100 and GA200 expressed in ORNs and a GA-specific antibody [32]. In agreement with our results using mCherry-tagged GA constructs, we found that the number of GA puncta detected outside of ORNs greatly increased with repeat length (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Since tags can interfere with protein function [31], we next tested the spread of untagged GA DPRs using GA100 and GA200 expressed in ORNs and a GA-specific antibody [32]. In agreement with our results using mCherry-tagged GA constructs, we found that the number of GA puncta detected outside of ORNs greatly increased with repeat length (Fig.…”
Section: Resultssupporting
confidence: 80%
“…We have shown that while tagging AKIR-1 or RPA-1 had no effect on viability, tagging of SYP-4 slightly reduced hatching rates, which may be due to mild defects in crossover formation. The fact that protein tagging may interfere with protein function is not unique to our system and is also true for any other tags, including small epitope tags [for example: (Goel et al 2000; Bucher et al 2002; Carson et al 2007; Thielges et al 2011; Saiz-Baggetto et al 2017)]. Introducing a small tag that allows live imaging, like we have shown, may also have an advantage in the case of proteins that do not tolerate large tags (such as full-length GFP).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of using different tags (even though they had little influence in our case) has been recently pointed out for high-throughput analyses [5456]. In the course of our research, an artefact was reported to affect the tagging of proteins [40], specifically, that a dramatic reduction occurred in the stability of tagged proteins due to the presence of a particular linker sequence in the 3HA module used for the Longtine system [41], for which it was reported that the use of a different linker sequence (as in our case) had less impact on the amount of proteins. It should be noted that a seminal study on the level of Clns [33] published by the Futcher laboratory did not use the Longtine tagging system but a genomic tagging approach [59] that also keeps 3’UTR sequences intact.…”
Section: Discussionmentioning
confidence: 78%
“…Although our results indicated that tag size does have a minor impact on the amount of Clb5, applying Occam’s razor principle for simplicity sake, we nevertheless decided to use the smaller 3HA tag. In the course of our research, it has been reported [40] that the 3HA module developed by Longtine et al [41] uses a linker between the protein to be tagged and the 3HA epitope that greatly affects the stability of the tagged protein. In our research we used the tool-box system [42], which uses a different linker that does not affect protein stability [40].…”
Section: Resultsmentioning
confidence: 99%